The Position of Traditional Anatolian Jewellery in the Jewellery Sector and Production Problems - Er, Birnaz (European Journal of Economics and Business Studies, 2016)
Traditional jewelry is a symbol of Anatolian culture. Anatolia has a rich identity in respect to handcrafts and nearly all of Anatolia districts have its own identical handicrafts. Jewelry is among this handicrafts that is produced only in special area and symbolizes its own region. Unfortunately, technological achievements adversely effects the traditional jewelry production such as, reducing the demands of them and decreased interest. The jewelry industry prefers the mass production techniques and this leads to destruction of traditional jewelry preferences. Nowadays, traditional jewelry is about to be destroyed. In this research, the position of traditional Anatolian jewelry in the jewelry sector will be investigated. In this context, firstly the Anatolian’s traditional jewelry will be introduced then, the position of traditional jewelry will be researched and the results will be explained, and suggestions for solutions will be presented.